Beyond the Classroom: Exploring Self-Directed Learning Strategies of an Indonesian Japanese Language Learner - Wury Dwiwardani; Setyaningsih, Wahyu Handayani; Wulandari, Retno Dewi (Universitas Negeri Semarang, 2025)
Advancements in technology, particularly the internet, have provided learners with extensive opportunities to access various resources for independent learning. However, not all learners can effectively utilize digital media and technology, and many face challenges in selecting appropriate materials and methods to support their learning. This study examines the self-directed learning strategies of a Japanese language learner, addressing the following questions: (1) What strategies are employed for independent learning? (2) What media are used, and how does he facilitate self-directed learning? This study employs a qualitative research approach, specifically narrative inquiry, to explore the learner’s experiences. Data were collected through semi-structured interviews and analyzed to identify patterns in self-directed learning strategies. Findings reveal that the learner adopt multiple strategies, including goal setting for both short-and long-term learning, adaptation, combination, evaluation, and validation. Additionally, the learner engages with various online resources, such as interactive learning platforms, receptive learning materials, social media, and authentic content. The study further identifies six key aspects of technology used in self-directed learning, with variations in frequency based on individual needs and perceived advantages and limitations.